PENGARUH INPUT DAN PRODUKSI SAWIT TERHADAP PDRB INDONESIA - Reza Juanda; Intan Mutia; Ahmad Fauzul Hakim Hasibuan (LPPM Universitas Malikussaleh – Indonesia, 2021)
This istudy iexamined ithe iinfluence iof ilabor, iland iarea, iand itheiamount iof ioil ipalm iproduction ion iGross iRegional iDomesticiProduct i(GRDP) iin iIndonesia. iThis istudy iused ithe ipanel idataimethod ito idetermine ithe ieffect iof iindependent ivariables ionidependent ivariables. iThe idata iused iwas isecondary idata ifrom i2015ito i2018. iThe iresults ishowed ithat ilabor iand ithe iamount iofiproduction isignificantly iinfluenced iGRDP, iwhile ithe iland iarea ihadino isignificant ieffect ion iGRDP.